Analisis Peran Sektor Unggulan Terhadap Struktur Perekonomian Berdasarkan Pendekatan Shift–Share di Provinsi Sumatera Utara Tahun 2008-2012 - Saragih, Trie Kartika Yanti; Edwina, Susy; ', Yusmini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Leading sectors has significan contribution economic growth and chages in economic structure. The objective of the study is to analysis economic structure based on PDRB, its role on economic growth, the chages in economic sectors and factor affecting economic growth in North Sumatera Province 2008-2012. This study uses secondary data in a time series for five years. The method of analysis used in this study is an analytical Location Quotient method and Shiftshare Approach method. The results show and know that the structure of the economy in North Sumatera Province have increased and more rapid growth occurs. Through analysis Location Quotient, there is a shift in economic structure from primary sector to secondary and tertiary sectors. The leading sector has an important role on growth of economic structure. Keywords: Economic Structure, Leading Sector, Location Quotient, Shiftshare.